The Role of Traditional Environmental Knowledge in Taytnapam Toponyms - Eugene S. Hunn; Richard H. McClure Jr. (Revue d'ethnoécologie)
The Taytnapam are a poorly known Indigenous community of the Pacific Northwest region of the United States. They lived in the upper Cowlitz River watershed relatively undisturbed by Euro-American colonization until late in the 1800s, avoiding the more radical depopulation and dislocation suffered by neighboring Native communities due to introduced diseases and colonial settlement. A majority of descendants are now citizens of the Yakama Nation and the Cowlitz Indian Tribe. The linguist Melville Jacobs published a detailed inventory of Taytnapam place names dictated to him in 1927 by two elderly consultants in the local Ichishkíin (Sahaptin) dialect. A substantial fraction of these toponyms refer directly or indirectly to local plants and animals, illustrating the power of local environmental knowledge for anchoring Taytnapam to their traditional lands. Traditional geographic narratives, such as those of Taytnapam elders Jim Yoke and Louis Castama, served a critical pedagogical role in educating the young with respect to native livelihoods. Of an inventory of over 300 Indigenous Taytnapam toponyms, some 60 of these name plant or animal species while others highlight Traditional Environmental Knowledge with regard to key habitats and seasonal patterns. It is noteworthy that Taytnapam elders attribute these names to Coyote, primal messenger of the Creator, herald of the traditional law, tamánwit, which established proper order in the universe. The names are thus “not made by man.”